(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2020)
Dan Solomon’s study can be considered a deep skepticism about the very principles that unfortunately still animate architectural education today. The culture of the architectural expert and the embrace of a design process of impenetrable mystery accessible only to the practitioners constitute the very basic premise upon which architectural education rests today. Dan offers some troubling examples from the United States, but he also considers others from Paris and from Rome.